Metformin Preconditioning and Postconditioning to Reduce Ischemia Reperfusion Injury in an Isolated Ex Vivo Rat and Porcine Kidney Normothermic Machine Perfusion Model. Issue 1 (31st July 2020) - Huijink, Tobias M.; Venema, Leonie H.; Posma, Rene A.; de Vries, Nynke J.; Westerkamp, Andrie C.; Ottens, Petra J.; Touw, Daan J.; Nijsten, Maarten W.; Leuvenink, Henri G.D.
Abstract : Metformin may act renoprotective prior to kidney transplantation by reducing ischemia‐reperfusion injury (IRI). This study examined whether metformin preconditioning and postconditioning during ex vivo normothermic machine perfusion (NMP) of rat and porcine kidneys affect IRI. In the rat study, saline or 300 mg/kg metformin was administered orally twice on the day before nephrectomy. After 15 minutes of warm ischemia, kidneys were preserved with static cold storage for 24 hours. Thereafter, 90 minutes of NMP was performed with the addition of saline or metformin (30 or 300 mg/L). In the porcine study, after 30 minutes of warm ischemia, kidneys were preserved for 3 hours with oxygenated hypothermic machine perfusion. Subsequently, increasing doses of metformin were added during 4 hours of NMP. Metformin preconditioning of rat kidneys led to decreased injury perfusate biomarkers and reduced proteinuria. Postconditioning of rat kidneys resulted, dose‐dependently, in less tubular cell necrosis and vacuolation. Heat shock protein 70 expression was increased in metformin‐treated porcine kidneys. In all studies, creatinine clearance was not affected. In conclusion, both metformin preconditioning and postconditioning can be done safely and improved rat and porcine kidney quality. Because the effects are minor, it is unknown which strategy might result in improved organ quality after transplantation.